Ecological Differentiation in Two Major Freshwater Bacterial Taxa Along Environmental Gradients - Nuy, Julia K.; Hoetzinger, Matthias; Hahn, Martin W.; Beisser, Daniela; Boenigk, Jens (Frontiers in Microbiology, 2020)
Polynucleobacter (Burkholderiaceae, Betaproteobacteria) and Limnohabitans (Comamonadaceae, Betaproteobacteria) are abundant freshwater bacteria comprising large genetic and taxonomic diversities, with species adapted to physico-chemically distinct types of freshwater systems. The relative importance of environmental drivers, i.e., physico-chemistry, presence of microeukaryotes and geographic position for the diversity and prevalence has not been investigated for both taxa before. Here, we present the first pan-European study on this topic, comprising 255 freshwater lakes. We investigated Limnohabitans and Polynucleobacter using an amplicon sequencing approach of partial 16S rRNA genes along environmental gradients. We show that physico-chemical factors had the greatest impact on both genera. Analyses on environmental gradients revealed an exceptionally broad ecological spectrum of operational taxonomic units (OTUs). Despite the coarse resolution of the genetic marker, we found OTUs with contrasting environmental preferences within Polynucleobacter and Limnohabitans subclusters. Such an ecological differentiation has been characterized for PnecC and LimC before but was so far unkown for less well studied subclusters such as PnecA and PnecB. Richness and abundance of OTUs are geographically clustered, suggesting that geographic diversity patterns are attributable to region-specific physico-chemical characteristics (e.g., pH and temperature) rather than latitudinal gradients or lake sizes.